FATAL CATTLE ATTACKS - AN OCCUPATIONAL HAZARD AMONG CATTLE REARERS (Journal of Forensic Medicine & Toxicology, 2025)
Animals, especially cattle, have long been integral to many cultures and vital to rural populations’ daily lives. However, these cattle sometimes turn violent and attack, causing severe life-threatening injuries with their various appendages, resulting in high-energy body trauma. The present article discusses series of four occupational fatalities cases among untrained cattle rearers due to cattle attacks. A fifty-year-old farmer was attacked by his bull when he was taking the bull for tying at the cattle pen, suffering chest injuries. In another incident, while rearing a bull, the bull attacked a thirty-four-year-old female farmer, and she suffered neck and spinal injuries and succumbed to the injuries six days later. A sixty-six year-old farmer shifting a pregnant cow for the cattle pen was stomped on and suffered fatal head and spinal injuries. A forty-two-year-old male was herding his cows along a state highway road when suddenly, one cow strayed towards the middle of the road. In order to get it back, he went towards the cow but was hit by an oncoming bus. He died due to fatal head and chest injuries. Various risk factors contribute to such occupational hazards among cattle rearers, such as inadequate facilities, fencing, gates, and poorly designed feeding and breeding areas. Other factors include working alone and improper handling techniques. Governments should provide proper cattle handling training and focus on cattle-related incidents as these high-velocity traumas pose great danger to human life. The authors also enlist strategies to minimize the risk of fatal cattle attacks among cattle rearers.
Keywords: cattle; attack; trauma; injuries; chest; spinal; head; occupational hazard